Using Assistive Technology to Differentiate and Accommodate Students with Special Needs Facing Learning Difficulties in Mathematics (Journal of Asian Development Studies, 2024)
This paper will discuss how assistive technology forms the basis of differentiation and support for students with special needs when conquering specific math learning difficulties. The Department of Special Education utilized a quantitative research design to collect data from 240 teachers through a structured, self-developed questionnaire. The use of simple random sampling maximized representative samples and minimized biases. We established the effects of AT in terms of differentiated instruction, increased student engagement, and an inclusive learning environment. Teachers estimated complex mathematical concepts using AT tools, such as virtual manipulatives and educational apps, as easier to understand and improve student confidence and participation levels. Overall, the findings indicate a need for continuous teacher training and resource allocation to effectively integrate these into a holistic classroom experience. The conclusion is that integrating assistive technology into education is a gateway to ensuring that every special need student receives quality learning in mathematics, thus equalizing access to education. Recommendations call for investment in professional development of the teachers, adequate resources for AT tools, and inculcation of AT provision in curriculum design. Further research should investigate the long-term effects of AT on students' achievement in other subjects.